Collective Schema, As a New Concept Suggesting and a View to Proverbs from Cognitive Behavioral Point of View - Esat SANLI; Selim PISTOF (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Cognitive Behavioral Tharapy doctrine and clinical accumulation have shown that there is a causal link between moods, paradigms, and assessments. These cognitive contents are named as automatic thoughts and schemas. Rational- adaptive automatic thoughts and schemas while bring to person good mood, irrational-maladaptive automatic thoughts and schemas bring to patology. On the other hand this cognitive structures have fed by accepted culture by society and components of this culture such as songs and proverbs which possess necessity and rules. The basic aim of this study is put forth concept of collective schema which will be assessable content in Cognitive Behavioral Approach , and clarifying bases of this concept deal with proverbs. In this sense, adaptive and maladaptive aspects of collective shema concept, have been commented, cognitive disortions which fed by maladaptive schemas deal with collective aspect, have been categorised and illustrated with proverbs. With this study we aimed create a groundwork for previous studies. [JCBPR 2016; 5(2.000): 85-93]